Os fundamentos da Constituição Subjetiva segundo Laplanche - Campos, Érico Bruno Viana [UNESP] (Instituto Educacional Piracicabano da Igreja Metodista, 2012)
Article presents the concept of subjectivity in the theory of Jean Laplanche from his questioning of metapsychology´s drive theory which led to the proposal of the theory of generalized seduction. The objective is to show how in this conception otherness is presented in a traumatic way in the primary constitution of subjectivity, endorsing certain positions in the psychoanalytic literature that advocate symbolic violence as a fundamental aspect of the subject of psychoanalysis.

Este artigo apresenta a concepção de subjetividade na teoria de Jean Laplanche a partir de sua problematização da teoria das pulsões na metapsicologia que levou à proposta da teoria da sedução generalizada. O objetivo é mostrar como nessa concepção a alteridade se apresenta de forma traumática na constituição originária da subjetividade, endossando certas posições na literatura psicanalítica que defendem a violência simbólica como aspecto fundamental do sujeito do inconsciente.
The foundations of Subjective Constitution According to Laplanche
Keywords: Psychoanalysis; Jean Laplanche; Otherness; Generalized seduction; Psicanálise; Jean Laplanche; Alteridade; Sedução generalizada